The determinants of positive creative adaptation of youth in the Polish-Czech borderland - Szczurek-Boruta, Alina (Creativity Studies, 2021)
The article is aimed at diagnosing the determinants of youth’s positive adaptation to changing demands of life. It is focused on the relationships between creativity and resilience. The analysis comprised youth’s adaptive competences and the resources and risks of social environment. In two measurement periods, quantitative-qualitative studies were conducted among youth in the Polish-Czech borderland. The research design enabled complex diagonal and longitudinal comparisons, which addressed: the identification and analysis of change trends, recognition of their lack, likelihood assessment of these trends in both compared cohorts. The concept of resilience was used to analyse and interpret research results. The identification was conducted of (outer and inner) risk and protective factors determining positive adaptation in the Polish-Czech borderland. The borderland effect was indicated – the impact of borderland on its inhabitants’ socialization, conditioned by spatial-social-cultural-economic properties. Attention was drawn to the forming of youth’s flexibility, ability to handle everyday situations and their resistful behaviour patterns. Borderland is a source and stimulant for acquiring the disposition of resilience. The presented analyses show tendencies and universal mechanisms of human behaviour, not only in borderlands. The article indicates the need for educational activities developing and forming resilience, for elaborating intervention programmes based on better use (in adaptation) of resources and protective factors in the environment.